Pharmacoeconomics, Outcomes Research, Health Technology Assessment, Comparative Effectiveness, Patient Centered Outcomes Research in Latin America 2016: brief update - Augustovski, Federico Ariel (2016)
One more year has elapsed since our last issue of VIHRI focused on Latin America (LA). It has been a very active year in our field in LA. Though in even years there is no regional ISPOR meeting, and we wait for the one to be held in Brazil in 2017, there has been considerable activity in Pharmacoeconomics, Outcomes Research, Health Technology Assessment, Comparative Effectiveness, Patient Centered Outcomes Research and other overlapping descriptors our broad field adopts. We will briefly review some LA highlights in our field, and then go over some specific aspects on VIHRI in general, and on this LA issue in particular.